If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 = -4 + -2x Reorder the terms: 2 + x = -4 + -2x Solving 2 + x = -4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 2 + x + 2x = -4 + -2x + 2x Combine like terms: x + 2x = 3x 2 + 3x = -4 + -2x + 2x Combine like terms: -2x + 2x = 0 2 + 3x = -4 + 0 2 + 3x = -4 Add '-2' to each side of the equation. 2 + -2 + 3x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -4 + -2 3x = -4 + -2 Combine like terms: -4 + -2 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| (x+4)(2x+2)= | | x^2-2x+400=0 | | 25=5+.50x | | (q-3)*2=16 | | 12x-31=38+9x | | 5x+3=-x+21 | | 2x(4x-7)= | | 8+p=9 | | -x-17=11-2x | | 3-v+3=1-4v+1 | | -66+x=9x+62 | | 16x+21=46-y | | -7=-7x-3(-x+17) | | G=7F+6 | | -34-8x=29-11x | | 79x^2-200x+125=0 | | x+7+3x=13+x | | 6(a-3)= | | 45-33x+33-44x=-45+33x-33+44x | | 11x-11=7x+12 | | 4j+4=6 | | 6y-5=3+4y | | 3x^2y^4+7x^2y^4-10x^4y^2= | | 3k+5-k=-9 | | -2x=160 | | 2((x-2)/2)=0 | | 2((x-2)/2) | | 45-33x+33-44=-45+33x-33+44x | | 3y-3=14 | | -7x-3+6x=-8x+9 | | 12x+18y=50 | | -10x+10x-10x= |